Unbiased proteomic profiling of host cell extracellular vesicle composition and dynamics upon HIV‐1 infection. (11th March 2021) - Martin‐Jaular, Lorena; Nevo, Nathalie; Schessner, Julia P; Tkach, Mercedes; Jouve, Mabel; Dingli, Florent; Loew, Damarys; Witwer, Kenneth W; Ostrowski, Matias; Borner, Georg H H; Théry, Clotilde
Abstract: Cells release diverse types of extracellular vesicles (EVs), which transfer complex signals to surrounding cells. Specific markers to distinguish different EVs (e.g. exosomes, ectosomes, enveloped viruses like HIV) are still lacking. We have developed a proteomic profiling approach for characterizing EV subtype composition and applied it to human Jurkat T cells. We generated an interactive database to define groups of proteins with similar profiles, suggesting release in similar EVs. Biochemical validation confirmed the presence of preferred partners of commonly used exosome markers in EVs: CD81/ADAM10/ITGB1, and CD63/syntenin. We then compared EVs from control and HIV‐1‐infected cells. HIV infection altered EV profiles of several cellular proteins, including MOV10 and SPN, which became incorporated into HIV virions, and SERINC3, which was re‐routed to non‐viral EVs in a Nef‐dependent manner. Furthermore, we found that SERINC3 controls the surface composition of EVs. Our workflow provides an unbiased approach for identifying candidate markers and potential regulators of EV subtypes. It can be widely applied to in vitro experimental systems for investigating physiological or pathological modifications of EV release. SYNOPSIS: Specific markers to distinguish extracellular vesicle (EV) diversity released at homeostasis or pathophysiological perturbation are currently lacking. This profiling/network analysis establishes a proteomic workflow to characterise the EV protein inventory of human T cells before and after infection by HIV‐1. Centrifugal separation of EV subtypes from Jurkat T cells allows quantitative proteomic profiling without additional purification. An interactive database calculates nearest neighbours of each EV‐protein and plots respective protein networks. Proteomic profiling of EVs under two experimental conditions allows identification of EV subtype‐specific modifications in protein composition. Comparative profiling of EVs from HIV‐1‐infected versus control Jurkat T cells reveals alterations in host cell protein inclusion into viral particles. Abstract : A new proteomic approach allows comprehensive characterisation of exosome heterogeneity in human T cells.